A carboxylesterase-activatable near-infrared phototheranostic probe for tumor fluorescence imaging and photodynamic therapy. Issue 54 (12th December 2022) - Li, Lihong; Zhang, Qi; Li, Jiaojiao; Tian, Yafei; Li, Jinyao; Liu, Wen; Diao, Haipeng
Abstract : A carboxylesterase-responsive near-infrared phototheranostic probe is developed, which has been employed for activatable fluorescence imaging of tumor cells. The probe triggers significant cell death upon 660 nm laser, with low cytotoxicity in dark. Abstract : Phototheranostic probes have been proven to be a promising option for cancer diagnosis and treatment. However, near-infrared phototheranostic probes with specific tumor microenvironment responsiveness are still in demand. In this paper, a carboxylesterase (CES)-responsive near-infrared phototheranostic probe was developed by incorporating 6-acetamidohexanoic acid into a hemicyanine dye through an ester bond. The probe exhibits highly sensitive and selective fluorescence enhancement towards CES because CES-catalyzed cleavage of the ester bond leads to the release of the fluorophore. By virtue of its near-infrared analytical wavelengths and high sensitivity, the probe has been employed for endogenous CES activatable fluorescence imaging of tumor cells. Moreover, under 660 nm laser irradiation, the probe can generate toxic reactive oxygen species and efficiently kill tumor cells, with low cytotoxicity in dark. As far as we know, the probe was the first CES-responsive phototheranostic probe with both near-infrared analytical wavelengths and photosensitive capacity, which may be useful in the real-time and in situ imaging of CES as well as imaging-guided photodynamic therapy of tumors. Therefore, the proposed probe may have wide application prospect in cancer theranostics.